Pengabdian Guru di Pondok Pesantren Darul Qur’an Sapeken Sumenep - Mulyadi Mulyadi; Muhammad Husni (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Teacher community service activities in Islamic boarding schools (pesantren) play a strategic role in improving the quality of education, shaping the character of students, and strengthening the tradition of knowledge. This article discusses the forms of teacher community service at the Darul Qur'an Sapeken Islamic Boarding School in Sumenep, including the role of teachers as educators, mentors, role models, and promoters of a culture of literacy and religious moderation. This study uses a qualitative descriptive approach using observation, interviews, and documentation techniques. The results indicate that teacher community service significantly influences the improvement of the quality of learning, discipline, and morals of students. This article is expected to serve as a reference for Islamic boarding schools in developing more focused and sustainable community service programs. <input id="ext" type="hidden" value="1"> <input id="ext" type="hidden" value="1">